2010
DOI: 10.3390/s100504675
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Agarwood Oil Using an Electronic Nose

Abstract: Presently, the quality assurance of agarwood oil is performed by sensory panels which has significant drawbacks in terms of objectivity and repeatability. In this paper, it is shown how an electronic nose (e-nose) may be successfully utilised for the classification of agarwood oil. Hierarchical Cluster Analysis (HCA) and Principal Component Analysis (PCA), were used to classify different types of oil. The HCA produced a dendrogram showing the separation of e-nose data into three different groups of oils. The P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 11 publications
0
44
0
Order By: Relevance
“…Hidayat et al (2010) reported that agarwood oil grading has been traditionally performed by trained human graders (sensory panels). The disadvantages of this technique include subjectivity, poor reproducibility, time consumption and large labor expense (Keller, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hidayat et al (2010) reported that agarwood oil grading has been traditionally performed by trained human graders (sensory panels). The disadvantages of this technique include subjectivity, poor reproducibility, time consumption and large labor expense (Keller, 1999).…”
mentioning
confidence: 99%
“…The disadvantages of this technique include subjectivity, poor reproducibility, time consumption and large labor expense (Keller, 1999). A human nose cannot tolerate a high number of samples and work in continuous production because it fatigues rapidly with increasing number of samples (Hidayat et al, 2010;Keller, 1999). Identification of agarwood oil would seem to be impossible without the use of laboratory techniques (Barden et al, 2000).…”
mentioning
confidence: 99%
“…This transformation is defined in such a way that the first principal component has as high a variance as possible and each succeeding component in turn has the highest variance possible under the constraint that it be orthogonal to the preceding components. It is therefore known as an unsupervised data analysis method or algorithm since it "ignores" class labels [50][51][52]. In this research, PCA was used to remove any redundancy between the components of the projected vectors and reduce the dimension of the original dataset.…”
Section: Steps In Pattern Recognitionmentioning
confidence: 99%
“…In addition, the trained tea tasters cannot tolerate large numbers of samples because they fatigue rapidly with increasing number of samples (Hidayat et al, 2010).…”
Section: Introductionmentioning
confidence: 99%